2006
DOI: 10.1051/parasite/2006134321
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of Western Blotting in hepatic and pulmonary cystic echinococcosis

Abstract: Summary :Many serological tests are widely used in the diagnosis of cystic echinococcosis (CE), caused by the larval stages of Echinococcus granulosus. The present study was carried for differentiation between hepatic and pulmonary cystic echinococcosis by Western Blotting (WB). A total of 121 sera from patients with hepatic CE (37), pulmonary CE (31) and controls (53; consisting of six healthy, seven Hymenolepis nana infection, 20 hepatic and 20 pulmonary diseases other than CE) were examined. In all of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Se reported in these studies varied from 64.8% to 100%. Reasons for false negative results depend on several factors comprising cyst location other than the liver [ 12 , 13 ], early (CE1) and inactive (CE4 and CE5) cyst stages [ 14 16 ], serum collection before treatment [ 15 , 17 ], single and small cysts [ 17 ], and HF antigenic source variability [ 18 ]. Additionally, E. granulosus complex comprises several genotypes that potentially express different antigenic sets.…”
Section: Hydatid Fluidmentioning
confidence: 99%
“…Se reported in these studies varied from 64.8% to 100%. Reasons for false negative results depend on several factors comprising cyst location other than the liver [ 12 , 13 ], early (CE1) and inactive (CE4 and CE5) cyst stages [ 14 16 ], serum collection before treatment [ 15 , 17 ], single and small cysts [ 17 ], and HF antigenic source variability [ 18 ]. Additionally, E. granulosus complex comprises several genotypes that potentially express different antigenic sets.…”
Section: Hydatid Fluidmentioning
confidence: 99%
“…Conducted in our country, CH is higher in women than in men. [3,16,17] According to the study of Hakverdi et al [18] according to their study, the rate of CH was found to be 53.7% in women and 46.3% in men. In a study from the Central Anatolia Region, 56% of the patients diagnosed with CH were reported as female and 44% as male.…”
Section: Discussionmentioning
confidence: 97%
“…Another recommendation for performance is to use the WB (Western Blot) test as a secondary confirmatory test due to its high specificity of up to 100% (2,6,(21)(22)(23)(24). It is possible to find different results for each technique in the literature due to the aforementioned factors, especially the type of antigen used in the test (18,(25)(26)(27)(28)(29).…”
Section: Serological Testsmentioning
confidence: 99%
“…The most commonly used antigen source for this purpose in tests is hydatid cyst fluid (HCS). Overall, HCS provides higher sensitivity (80-99% sensitivity and 60-97% specificity), while tests in which the purified main antigenic structures of Antigen 5 (Ag5) and Antigen B (AgB) or their smaller subunits or their recombinant forms and synthetic peptides are used as antigens provide higher specificity (33-93% sensitivity and 80-100% specificity) (27)(28)(29)(30). A double-blind, randomized study on this subject compared the diagnostic performances of HCS, natural AgB, two recombinant AgB subunits, an AgB-derived synthetic peptide, and recombinant cytosolic malate dehydrogenase (EgM-DH) in the ELISA method (31).…”
Section: Serological Testsmentioning
confidence: 99%